Sragen Regency Government Concerning the Policy of Designating Protected Paddy Land in the Perspective of the Rule of Law - ponco Edi ahmad ponco; Lego Karjoko (Faculty of Law, Universitas Pekalongan, 2022)
Ensuring the well-being of the population requires the Sragen district government to prioritize food security as a crucial policy. However, the implementation of this policy faces challenges due to its conflict with the Sragen district Spatial Planning Regional Regulation. Consequently, it becomes imperative to thoroughly investigate the validity of the policy's stipulations. The purpose of this article is to elucidate the policy's validity, employing normative qualitative research methods, supplemented by statutory and conceptual approaches, and employing deductive analyzing information. The study's results suggest a noteworthy revelation that the policy concerning protected paddy fields was formulated without adhering to proper legal procedures, thereby rendering it invalid and failing to meet the necessary requirements.